Segmentary resection of the spleen: (calcified hematoma) - Puig, Roberto; Arce, Enrique; Gilardoni, Federico; Rodríguez de Vecchi, Victoriano (Cirugía del Uruguay, 1985)
Submitted for consideratlon at this Soclety, a prlmary observation of segmentary resection of the spleen in non traumatic pathology following Campos Christo's regulated technique. The nature of the process, interpreted as calcified hematoma, facllitated applicatlon of the "clivage" technique for maintenance of both poles. No complications were registered. Remole scintillographic control confirms the viability of non resected segments.